An HSP90 inhibitor based fluorescent probe for selective tumor targeting. (December 2021) - Zhu, Shulei; Lu, Yingxin; Jin, Jiyu; Yu, Jiahui; Lu, Wei
Abstract: Fluorescent imaging has been widely used in the detection of diseases, especially cancer. Among them, biomarker-specific ligand-based imaging strategies have attracted much attention, due to their improved image contrast and diagnostic accuracy. In this work, an HSP90 inhibitor based fluorescent probe (Probe 1 ) was synthesized possessing the potential of selective tumor targeting, which was constructed with an HSP90 inhibitor and ﻿4-hydroxy-1, 8-naphthalimide derivative. ﻿Probe 2, a resorcinol-blocked probe was also synthesized as a control, which prevented binding with the HSP90 ATP binding pocket. Biological studies showed that Probe 1 could ﻿be selectively accumulated by tumor cells, while Probe 2 not, suggesting that Probe 1 is a promising ﻿targeted tumor imaging agent for ﻿early diagnosis. Graphical abstract: Image 1 Highlights: Probe 1 retains HSP90 affinity while Probe 2 not. Probe 1 was demonstrated to have HSP90-dependent and time-dependent cellular uptake mechanism. Probe 1 showed enhanced tumor-targeting behavior. Probe 1 can be considered as a potential tumor targeting probe in fluorescent imaging.